Water colder than boreal snow: an analysis of the motif of drinking cold water in the epigrams of Leonidas of Tarentum - Orłowska, Ewa (Sapiens ubique civis, 2023)
In this paper I analyse the motif of drinking cold water in the poems of Leonidas of Tarentum, showing the relation of his epigrams to the works of Anyte and of other Hellenistic poets, focusing on metaphorical and programmatic meaning. Epigrams 16 and 18 GP of Anyte are interpreted as opening poems of a collection. The famous metaphor of drinking from the sacred fountain, instead of a polluted river, comes from Callimachus Hymn 2, 108–112, which is similar to the opposition in Leonidas’ 86 GP. The ecphrasis of a cup represents poetic work in Theocritus Idyll 1. By comparing these texts, I argue that epigrams of Leonidas are related not only with Anyte’s poems, but also with the works of other Hellenistic authors and the drinking motif should be read metaphorically, as referring to poetic activity, not as a simple bucolic scene.